Suitability of Content in Textbook “English for Nusantara” for Junior High School - Na'imatul Husni (Universitas Indo Global Mandiri, 2025)
This research focuses on the analysis of textbooks intended for 9th-grade junior high school students, which are specifically designed according to the latest curriculum known as the Merdeka curriculum. The purpose of this study is to determine the suitability of the textbook content for 8th-grade students based on Thomlinson's theory. The main data source for this study is the English textbook